The potential of space observations for pulsating pre-main sequence stars - Zwintz Konstanze (EPJ Web of Conferences, 2017)
The first asteroseismic studies of pre-main sequence (pre-MS) pulsators have been conducted based on data from the space telescopes MOST and CoRoT with typical time bases of less than 40 days. With these data, a relation between the pulsational properties of pre-MS δ Scuti stars and their relative evolutionary phase on their way from the birthline to the zero-age main sequence was revealed. But it is evident from comparison with the more evolved pulsators in their main sequence or post-main sequence stages observed by the main Kepler mission, that many more questions could be addressed with significantly longer time bases and ultrahigh precision. Here, I will discuss the observational status of pre-MS asteroseismology and the potential of future space observations for this research field.